Atorvastatin reverses high cholesterol‐induced cardiac remodelling and regulates mitochondrial quality‐control in a cholesterol‐independent manner: An experimental study. (25th May 2021) - Zheng, Peng; Ding, Yanzi; Lu, Feiyan; Liu, Nannan; Wu, Hengfang; Bian, Zhiping; Chen, Xiangjian; Yang, Di
Abstract: Mitochondria are key regulators of cell fate, maintaining self‐stability by a fine‐tuned quality‐control network including mitophagy, biogenesis, fission and fusion processes. Myocardial mitochondria can be impaired by hypercholesterolemia. Statins, such as atorvastatin, are considered the cornerstone in the management of hypercholesterolaemia primarily due to their marked cholesterol‐lowering ability. The direct effect of atorvastatin on myocardial mitochondria remains unclear. We aimed to explore whether atorvastatin could attenuate myocardial mitochondrial defects induced by high cholesterol, and whether cycloastragenol, a potent telomerase activator, could be used as a potential complementary bioactive compound for obesity and hypercholesterolaemia treatment. We found that atorvastatin at a low dose (3 mg/kg) did not reduce elevated serum cholesterol, but reversed cardiac remodelling and dysfunction in C57BL/6J mice fed with high‐fat diet (HFD). Atorvastatin reversed the upregulated mitophagy, mitochondrial fission and fusion, accompanied by mitochondrial biogenesis activation in HFD‐fed mice hearts. Mitochondrial structural impairments were attenuated by atorvastatin in HFD‐fed mice and oxidized low‐density lipoprotein (ox‐LDL) exposed HL‐1 cardiomyocytes. The depolarized mitochondrial membrane potential and increased mitochondrial oxygen consumption rates in ox‐LDL exposed HL‐1 cells were recovered by atorvastatin. Furthermore, atorvastatin co‐treated with cycloastragenol had better effects on reducing body weight, improving cardiac remodelling and dysfunction, and protecting mitochondria in high cholesterol. Conclusively, low‐dose atorvastatin exhibited a cholesterol‐independent cardioprotective effect through improving the mitochondrial quality‐control network and repairing mitochondrial ultrastructure in high cholesterol. Atorvastatin plus cycloastragenol supplement therapy has a better effect on treating obesity and hypercholesterolaemia.